Konstruksi Model Pengujian Ex Ante terhadap Rancangan Undang-Undang di Indonesia - W. Nalle, Victor Imanuel (Jurnal Konstitusi, 2013)
The quality of legislation in Indonesia is often questioned when the Constitutional Court cancels several chapters of a law or even the entire law.  The poor quality of legislation is influenced by powerful political factor in the legislation process. These factors have an impact on unsynchronization of laws with the constitution   or disharmony with other legislation. Ex ante review in this context becomes an alternative way to prevent bad legislation because every bill should be reviewed first. In Indonesian context, the ideal model of ex ante review is not only concerning with the constitutionality, but also harmony with other laws as well as other parameters necessary to produce good  legislation.